1980
DOI: 10.3758/bf03198688
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stimulus duration on the persistence of gratings

Abstract: The persistence of gratings varying in spatial frequency and exposure duration was measured using a stimulus-blank alternation method. Persistence was found to lengthen with increasing spatial frequency and to shorten with increasing exposure duration. For each spatial frequency, persistence decreased linearly with a slope of approximately-.75 as duration increased for short stimulus durations. For longer stimulus durations, the rate of decline in persistence with increasing duration was reduced, the slope bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 21 publications
6
32
0
Order By: Relevance
“…These investigators reported that the lSI at which transitions from element to group motion occurs tends to increase as the spatial frequencies composing each frame of the alternating displays decrease. On the basis of our persistence hypothesis and the finding that persistence decreases as spatial frequency decreases (Bowling & Lovegrove, 1980;Breitmeyer et al, 1981;Meyer & Maguire, 1977), one would expect the opposite result, namely, that the transitional lSI decreases as spatial frequency decreases.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These investigators reported that the lSI at which transitions from element to group motion occurs tends to increase as the spatial frequencies composing each frame of the alternating displays decrease. On the basis of our persistence hypothesis and the finding that persistence decreases as spatial frequency decreases (Bowling & Lovegrove, 1980;Breitmeyer et al, 1981;Meyer & Maguire, 1977), one would expect the opposite result, namely, that the transitional lSI decreases as spatial frequency decreases.…”
Section: Discussionmentioning
confidence: 83%
“…This result again is in agreement with our persistence hypothesis. Bowling and Lovegrove (1980) demonstrated that visual persistence of grating stimuli is affected interactively by spatial frequency and duration. They found, in agreement with our results and interpretation, that increases of duration decreased visual persistence more when high-spatial-frequency gratings (small patterns) were employed than when low-frequency ones were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, they have shown that the transitional ISI is a decreasing function of viewing eccentricity, element size, and frame duration. These three variables are all negatively correlated with measures of the visual iconic persistence (Bowen, Pola, and Matin, 1974;Bowling and Lovegrove, 1980;Breitmeyer and Halpern, 1978;Breitmeyer, Levi, and Harwerth, 1981;Di Lollo, 1977;Di Lollo and Hogben, 1985;Meyer and Maguire, 1977;Mezrich, 1984). None of these studies indicate, however how visual persistence should be modeled, how it may inhibit group motion, or why the illusory percept in element motion does not "collide" with the stationary dots and be thereby terminated.…”
Section: Motion Versus Visual Persistencementioning
confidence: 98%
“…As spatial frequency increases, so does persistence (Bowling & Lovegrove, 1980;Bowling, Lovegrove, & Mapperson, 1979;Lovegrove & Meyer, 1984;Meyer & Maguire, 1977). Persistence has also been shown to vary inversely with the contrast of the stimulus (Bowling & Lovegrove, 1980;Bowling et al, 1979;Marx & May, 1983). In the task in these studies, a briefly presented (50-msec) square-wave grating was cycled with a variable duration blank field of the same average lumiCopyright 1992 Psychonomic Society, Inc. 222…”
mentioning
confidence: 99%